Exogenous enzymes and irradiation of barley reduce the anti-nutritional activity of non-starch polysaccharides in broilers - Van Rensburg, Connie E.J. (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2008.